Cambridge dictionary of astronomy - Mitton, Jacqueline (Cambridge University Press, 2001)
This dictionary explains over 3000 of the most commonly encountered terms, names and abbreviations used today and in the past, covering both professional and amateur astronomy. It is primarily a dictionary of words particular to astronomy, but some relevant terms from physics and space science have been included to make it a useful one-stop reference source for a wide range of users.